2015
DOI: 10.1111/een.12241
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale migration synchrony between parasitoids and their host

Abstract: Abstract. 1. Parasitoids are a valuable group for conservation biological control. In their role as regulators of aphid pests, it is critical that their lifecycle is synchronised with their hosts in both space and time. This is because a synchronised parasitoid community is more likely to strengthen the overall conservation biological control effect, thus damping aphid numbers and preventing potential outbreaks. One component of this host-parasitoid system was examined, that of migration, and the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…Using a model that incorporated aphid and parasitoid responses, Hoover and Newman (2004) showed that climate change should not alter biological control of cereal aphids. Consistent with this, based on suction trap samples from 1976 to 2013 from two sites in Southern England, simple regression models showed that the peak parasitoid abundance was correlated with peak aphid abundance in this record (Perez-Rodriguez et al, 2015). Together, and based on the reports so far, there is little evidence that parasitism of aphids will be disrupted by climate change.…”
Section: 2014supporting
confidence: 56%
See 2 more Smart Citations
“…Using a model that incorporated aphid and parasitoid responses, Hoover and Newman (2004) showed that climate change should not alter biological control of cereal aphids. Consistent with this, based on suction trap samples from 1976 to 2013 from two sites in Southern England, simple regression models showed that the peak parasitoid abundance was correlated with peak aphid abundance in this record (Perez-Rodriguez et al, 2015). Together, and based on the reports so far, there is little evidence that parasitism of aphids will be disrupted by climate change.…”
Section: 2014supporting
confidence: 56%
“…Data sets of pest abundance or pest injury in wheat systems might exist that have yet to be analysed in conjunction with historical climate records. Several of the publications cited in Table 1, although relatively recent, draw upon such archival records (Bell et al, 2014;Brabec et al, 2014;Woli et al, 2014;Huang et al, 2015;Perez-Rodriguez et al, 2015). Where such historical records are lacking, they should be initiated without delay to enable projections as climate change progresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…braconids) are seen to function somewhat differently from predation by generalist arthropod predators such as ladybirds and spiders (Snyder & Ives, 2003). Analysis of samples from 1976 to 2013 from the RIS archive revealed a positive regulation of parasitoid braconid populations in response to their aphid host S. avenae (Perez-Rodriguez et al, 2015). There was also a broad synchronisation of the migration time of the parasitoids and that of the aphid within a season.…”
Section: The Use Of Sample Collections To Understand Ecological and Ementioning
confidence: 99%
“…Seasonal migration of herbivorous insects to new habitats, which provides “enemy‐free space”, has been considered as one of the avoidance behaviors that have evolved in the host in response to parasitism (Chapman, Reynolds, & Wilson, ). However, parasitoids may evolve to synchronize migration with their hosts (Pérez‐Rodríguez, Shortall, & Bell, ), and even ahead of their hosts (Bortolotto, Júnior, & Hoshino, ). For instance, some Aphidiinae parasitoids show long‐range dispersal in egg and larval stages through host flight as well as through active dispersal by adult parasitoids (Bortolotto et al., ; Derocles, Plantegenest, Chaubet, Dedryver, & Le Ralec, ).…”
Section: Introductionmentioning
confidence: 99%